Measurement of Natural Radioactivity Concentrations in Local and Imported Truffle Samples - Hussein, Mayameen; Jebur, Jabbar; badran, hussain (University of Thi-Qar Journal of Science, 2025)
In this study, gamma spectroscopy with NaI(Tl) was used to measure the specific activity of natural radio nuclides uranium, thorium, uranium potassium, radium equivalent, annual effective dose, and excess lifetime cancer risk (ELCR) of truffles from the north of Iraq to the south and from the east to the west, as well as samples that were brought in from other countries. The average concentrations of 226Ra, 238U, 232Th, and 40K were 1.32±0.089 Bq/kg, 1.37±0.092 Bq/kg, 1.56±0.119 Bq/kg, and 23.31±0.958 Bq/kg, respectively. It was found that the gamma ray hazard scores and the extra lifetime cancer risk were about the same as the world average.